Safety and effectiveness of transjugular renal biopsy for systemic lupus erythematosus and antiphospholipid antibody syndrome patients taking antithrombotics. Issue 10 (3rd June 2019) - Nielly, Hubert; Mathian, Alexis; Cazenave, Maud; Izzedine, Hassan; Haroche, Julien; Cohen-Aubart, Fleur; Hie, Miguel; Miyara, Makoto; Pineton de Chambrun, Marc; Benameur, Neila; Hausfater, Pierre; Pha, Micheline; et al.
Abstract: Background: Renal biopsy is the cornerstone of systemic lupus erythematosus (SLE) nephritis and antiphospholipid syndrome (APS) nephropathy management. However, transcutaneous renal biopsy (TCRB) is hampered by the antithrombotic treatment frequently prescribed for those diseases. Transjugular renal biopsy (TJRB) offers an attractive alternative for patients at increased risk of bleeding. The primary objective of the study was to describe the safety profile and diagnostic performance of TJRB in SLE and APS patients. Methods: All SLE and/or APS patients who underwent a renal biopsy in our department (between January 2004 and October 2016) were retrospectively reviewed. Major complications were death, haemostasis nephrectomy, renal artery embolization, red blood cell transfusion, sepsis and vascular thrombosis; macroscopic haematuria, symptomatic perirenal/retroperitoneal bleeding and renal arteriovenous fistula without artery embolization were considered as minor complications. Results: Two hundred and fifty-six TJRBs—119 without antithrombotics (untreated), 69 under aspirin and 68 on anticoagulants and 54 TCRBs without antithrombotics—were analysed. Their major and minor complication rates, respectively, did not differ significantly for the four groups: 0 and 8% for untreated TJRBs, 1 and 6% for aspirin-treated, 6 and 10% for anticoagulant-treated and 2 and 2% for TCRBs. The number of glomeruli sampled and the biopsy contribution to establishing a histological diagnosis was similar for the four groups. Conclusions: TJRBs obtained from SLE and APS patients taking antithrombotics had diagnostic yields and safety profiles similar to those of untreated TCRBs. Thus, TJRB should be considered for SLE and APS patients at risk of bleeding.